A study of Puerto Rico's banking system - DeBeers, John S. ([San Juan, P.R. : Finance Council, 1960)
This study reviews the nature of the financial services rendered by Banks to small business and the community in general, and it offers suggestions designed to improve further the already valuable contributions made by the Banks.
Includes bibliographical footnote and index.
hza 28/11/2018
Loans
Keywords: Banks and banking